(untitled) (International Journal of Engineering and Computer Science, 2018)
Data mining is an emerging topic of the computer science research in recent years, and it has extensive applications in various fields such as Bio informatics, Criminal investigation, Research analysis, Corporate surveillance, Manufacturing engineering, Web and Semantic web. It uses machine learning, statistical and visualization techniques to discovery and present knowledge in a form, which is easily and is well explicable to humans. In today’s ferociously competitive business surroundings, corporations to speedily flip these zettabytes of information into vital insights into their customers and markets to guide their promoting, investment and management ways. We are concentrating many taking survey for many data mining 102 software tools because however current information contains most structured and unstructured data, spatial data.etc., that it becomes almost not possible to manually analyze them for valuable decision-making information .Automated discovery tools have the aptitude to investigate the information and gift the extracted high level info to the analyst or decision-maker. This research paper focuses on data mining techniques, software tools, and most trendy applications.